A new species and a new record of Typhonium (Araceae) from southern Vietnam - Van, Hong Thien; Le, van Son; Nguyen-Phi, Nga; Nguyen, Quoc Dat; Nguyen, Tran Quoc Trung; Nguyen, Hieu Cuong; Luu, Hong Truong (Phytotaxa, 2021)
Typhonium vietnamense is described as a new species from Vietnam. It is most similar to Typhonium varians but differs in a combination of leafy and floral characters. In addition, T. khonkaenensis is newly recorded for Vietnam, leading to exclusion of T. violifolium from the national flora. An updated key to all known species of Typhonium in Vietnam is given.